2019
DOI: 10.1016/j.nicl.2019.101862
|View full text |Cite
|
Sign up to set email alerts
|

Cortical abnormalities in youth at clinical high-risk for psychosis: Findings from the NAPLS2 cohort

Abstract: In a recent machine learning study classifying “brain age” based on cross-sectional neuroanatomical data, clinical high-risk (CHR) individuals were observed to show deviation from the normal neuromaturational pattern, which in turn was predictive of greater risk of conversion to psychosis and a pattern of stably poor functional outcome. These effects were unique to cases who were between 12 and 17 years of age when their prodromal and psychotic symptoms began, suggesting that neuroanatomical deviance observabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 52 publications
5
38
0
Order By: Relevance
“…This might be explained by (1) normalization of cortical surface area when transitioning into adulthood; (2) cortical surface area alterations being only present in a specific subgroup (subtype) of adult patients with adolescent-onset MDD, which we were unable to detect; or (3) those with cortical surface area alterations in early adolescence may be at higher risk for transitioning from MDD to other mental disorders over time. This latter possibility is consistent with reports of lower cortical surface area in adolescents and adults with psychosis or schizophrenia 82,83 , and in individuals at high risk for and/or transitioning to psychosis 84,85 . Longitudinal studies are required to test the hypothesis that cortical surface area alteration is a pre-existing risk factor for the development of MDD, and to investigate the subsequent clinical course of these young people with MDD and global surface area reductions.…”
Section: Subcortical Brain Regionssupporting
confidence: 91%
“…This might be explained by (1) normalization of cortical surface area when transitioning into adulthood; (2) cortical surface area alterations being only present in a specific subgroup (subtype) of adult patients with adolescent-onset MDD, which we were unable to detect; or (3) those with cortical surface area alterations in early adolescence may be at higher risk for transitioning from MDD to other mental disorders over time. This latter possibility is consistent with reports of lower cortical surface area in adolescents and adults with psychosis or schizophrenia 82,83 , and in individuals at high risk for and/or transitioning to psychosis 84,85 . Longitudinal studies are required to test the hypothesis that cortical surface area alteration is a pre-existing risk factor for the development of MDD, and to investigate the subsequent clinical course of these young people with MDD and global surface area reductions.…”
Section: Subcortical Brain Regionssupporting
confidence: 91%
“…Two recent studies showcase the complex interactions of age with neuroanatomy and transition prediction. As detailed above, a larger gap between “brain age” and chronological age and was predictive of greater risk of transition to psychosis, was observed in the NAPLS 2 study; however, this effect was found only in patients diagnosed with CHR status at a young age (i.e., 12–17 years), while it was not present in patients diagnosed at a later age [ 86 ]. Another long-term follow-up study [ 186 ] reported that surface area decreases in the prefrontal, cingulate, and parahippocampal areas predicted poor symptomatic outcomes in younger, but not in older CHR adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Other implementations of machine-learning models include their use to investigate age-related maturation of brain structure, which has been reported to follow deviant patterns in CHR patients. The North American Prodrome Longitudinal study (NAPLS 2) used structural MRI scans [ 86 ] of healthy individuals ( n = 190) to develop age prediction models, and subsequently calculated the gap between model-predicted age and chronological age in CHR patients ( n = 380); the Personalized Prognostic Tools for Early Psychosis Management study (PRONIA) implemented a similar approach on neurocognitive performance data of 36 healthy individuals and 48 CHR patients [ 87 ]. A larger “brain-age” gap in CHR patients, which was predictive of greater risk of transition to psychosis, was observed in the NAPLS 2 study [ 86 ].…”
Section: Structural Neuroimagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Very interestingly, the degree and timing of grey matter loss may depend on age of symptom onset. In a recent report, Chung et al evaluated baseline MRI parameters of converters and non-converters and observed that younger CHR subjects (12–17 years old) that converted to psychosis exhibited decreased grey matter volume at baseline and a less steep grey matter decline at first episode psychosis ( 134 ). However, older CHR subjects (> 18yrs old) that converted to psychosis did not have decreased grey matter volume at baseline, but exhibited a much steeper rate of volume loss as illness progressed.…”
Section: Discussionmentioning
confidence: 99%